Structure elucidation and docking analysis of 5M mutant of T1 lipase Geobacillus zalihae - Ishak, Siti Nor Hasmah; Ahmad Kamarudin, Nor Hafizah; Mohamad Ali, Mohd Shukuri; Leow, Adam Thean Chor; Mohd Shariff, Fairolniza; Raja Abd Rahman, Raja Noor Zaliha (Public Library of Science, 2021)
5M mutant lipase was derived through cumulative mutagenesis of amino acid residues (D43E/T118N/E226D/E250L/N304E) of T1 lipase from Geobacillus zalihae. A previous study revealed that cumulative mutations in 5M mutant lipase resulted in decreased thermostability compared to wild-type T1 lipase. Multiple amino acids substitution might cause structural destabilization due to negative cooperation. Hence, the three-dimensional structure of 5M mutant lipase was elucidated to determine the evolution in structural elements caused by amino acids substitution. A suitable crystal for X-ray diffraction was obtained from an optimized formulation containing 0.5 M sodium cacodylate trihydrate, 0.4 M sodium citrate tribasic pH 6.4 and 0.2 M sodium chloride with 2.5 mg/mL protein concentration. The three-dimensional structure of 5M mutant lipase was solved at 2.64 Å with two molecules per asymmetric unit. The detailed analysis of the structure revealed that there was a decrease in the number of molecular interactions, including hydrogen bonds and ion interactions, which are important in maintaining the stability of lipase. This study facilitates understanding of and highlights the importance of hydrogen bonds and ion interactions towards protein stability. Substrate specificity and docking analysis on the open structure of 5M mutant lipase revealed changes in substrate preference. The molecular dynamics simulation of 5M-substrates complexes validated the substrate preference of 5M lipase towards long-chain p-nitrophenyl–esters.